Genres: A Proposal for Application in ESP Courses - Ramos, Rosinda de Castro Guerra (The ESPecialist, 2012)
The motivation for this study is my work in ESP contexts, more specifically in the area of teacher development and course design, where the theoretical views of genre find the ideal place for its application. Although much has been written about genres (Swales, 1990; Askehave & Swales, 2001; Bhatia, 1993; Martin, 1984, 2000; Eggins & Martin, 1997; Marcuschi, 2002, among others), little has been done in pedagogical contexts (Cristovão, 2002; Castro, 2003; Cardoso, 2003; Vian Jr, 2003). This study may bring a contribution for this area, presenting a pedagogical suggestion for the implementation of genrebased tasks in the classroom. This article presents ways in which genres may be exploited in the ESP classroom. First, the concept of genre that underlies the pedagogical suggestion is presented, and objectives and types of activities to be considered for such an implementation. Next, the three phases suggested for the development of the work in the classroom are presented, as well as the components to be exploited: contents, their reasons and examples of possible activities to be used in the classroom.